Implementasi Pendidikan Akhlak Integratif-Inklusif - Muhammad Syafiqurrohman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2020)
Integrative-inclusive moral education can be interpreted as a formulation of a broad and holistic moral education process. Moral education materials can work together with all subjects, school culture, extracurricular activities, and even with the community. It is said that the integrative scientific structure does not mean that the various sciences are merged into an identical form of science, but rather the character, style, and nature of the science are integrated in the unity of the spiritual material dimensions, revelation, secularl-religion, physical-spiritual, and the world hereafter. Integration requires the existence of a relationship or unification or synchronization or greet each other or alignment between each existing scientific fields. Each scientific field cannot stand alone, without greeting each other with other scientific fields. While inclusive education, is a matter relating to many aspects of human life based on the principles of equality, justice, and individual rights. So integrative-inclusive education means that an educational process must cover a broad and comprehensive scope. Integrative-inclusive moral education has a holistic scope. Keywords: Moral education, integrative-inclusive Abstrak Pendidikan akhlak integratif-inklusif dapat dimaknai sebagai suatu rumusan proses pendidikan akhlak yang dilakukan secara luas dan holistik. Materi pendidikan akhlak dapat bersinergi dengan seluruh mata pelajaran, budaya sekolah, kegiatan ekstrakurikuler, serta dengan komunitas. Dikatakan struktur keilmuan integratif bukan berarti antara berbagai ilmu tersebut dilebur menjadi satu bentuk ilmu yang identik, melainkan karakter, corak, dan hakikat antara ilmu tersebut terpadu dalam kesatuan dimensi material spiritual, akal-wahyu, ilmu umum-ilmu agama, jasmani-rohani, dan dunia akhirat. Integrasi menghendaki adanya hubungan atau penyatuan atau sinkronisasi atau saling menyapa atau kesejajaran antar tiap bidang keilmuan yang ada. Setiap bidang keilmuan tidak dapat berdiri sendiri, tanpa saling menyapa dengan bidang keilmuan yang lain. Sedangkan pendidikan inklusif, merupakan suatu hal yang berkaitan dengan banyak aspek hidup manusia yang didasarkan atas prinsip persamaan, keadilan, dan hak individu. Maka pendidikan integratif-inklusif memiliki makna bahwa suatu proses pendidikan harus mencakup ruang lingkup yang luas dan menyeluruh. Pendidikan akhlak secara integratif-inklusif memiliki cakupan yang menyeluruh dan holistik. Kata Kunci: Pendidikan akhlak, integratif-inklusif